A telluride shell on plasmonic Au nanoparticles: amorphous/crystalline phase and shape evolution engineering via aqueous cation exchange. (21st April 2021) - Su, Mengyao; Li, Xinyuan; Xu, Meng; Wan, Xiaodong; Wang, Hongzhi; Bai, Bing; Rong, Hongpan; Liu, Jiajia; Liu, Jia; Zhang, Jiatao
Abstract : Using aqueous cation exchange synthesis strategy for the first time, we have synthesis Au@PbTe core–shell nanocrystals with engineering of amorphous/crystalline phase and shape evolution facilely. Abstract : Lattice-mismatch-directed hybrid metal@semiconductor core–shell nanocrystals with extended scope of diversity in composition and morphologies are critical to create more function integrations and applications. The case of metal@telluride hetero-nanostructures are more typical due to the electronegativity and electron affinity of tellurium, which are impediment of the telluride shell synthesis in the aqueous phase. Herein, we take advantage of the aqueous cation exchange (ACE) synthetic strategy, have synthesized Au@PbTe core–shell nanocrystals with engineering of amorphous/crystalline phase and shape evolution facilely. By controlling the kinetics of the ACE-enabled hydrothermal CE strategy and the starting phase/composition of Au@Ag2 Te nanostructures, we also achieved core–shell to yolk–shell evolution with different Au core sizes and hollow PbTe shells. These plasmonic core–shell nanostructures with a suitable telluride shell thickness demonstrated potential applications in surface enhanced Raman scattering.